Determinants of Tax Aggressiveness in Food and Beverage Subsector Companies - Siska Agustina Kusumastuti; Yuli Chomsatu Samrotun; Riana Rachmawati Dewi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to test and analyze the influence of liquidity, CSR, ROA, company size and capital intensity on the tax aggressiveness of food and beverage subsector companies listed on the IDX from 2019 to 2019. 2022. The population in this research is the food and beverage subsector companies registered on the IDX during the 2019-2022 period, totaling 24 companies. Sampling used a non-probability sampling method with a purposive sampling technique of 15 companies. The data source is secondary data accessed via www.idx.co.id. The data analysis technique used in this research uses multiple regression analysis. The results of this study show that ROA influences tax aggressiveness. Meanwhile liquidity, CSR, company size and capital intensity do not affect tax aggressiveness.